2017
DOI: 10.1093/nar/gkx579
|View full text |Cite
|
Sign up to set email alerts
|

HMGN1 and 2 remodel core and linker histone tail domains within chromatin

Abstract: The structure of the nucleosome, the basic building block of the chromatin fiber, plays a key role in epigenetic regulatory processes that affect DNA-dependent processes in the context of chromatin. Members of the HMGN family of proteins bind specifically to nucleosomes and affect chromatin structure and function, including transcription and DNA repair. To better understand the mechanisms by which HMGN 1 and 2 alter chromatin, we analyzed their effect on the organization of histone tails and linker histone H1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
66
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(77 citation statements)
references
References 62 publications
(132 reference statements)
11
66
0
Order By: Relevance
“…On the other hand, anti-H1 staining of interphase chromatin appears to migrate with the chromatin toward the nuclear envelope, when treated with 300 mM sucrose ( Figure 6(b)). The HMG non-histone proteins constitute a family of proteins (in lesser amounts than H1 histones) which bind to nucleosomes and modulate chromatin higher-order structure and functions [38][39][40]. Figure 6 presents immunostaining data for two HMG proteins (HMGN2 and HMGB2), illustrating the patterns in 0 mM and in 300 mM sucrose.…”
Section: Ki67 Segregates From Hyperosmotic Sucrose Congealed Mitotic mentioning
confidence: 99%
“…On the other hand, anti-H1 staining of interphase chromatin appears to migrate with the chromatin toward the nuclear envelope, when treated with 300 mM sucrose ( Figure 6(b)). The HMG non-histone proteins constitute a family of proteins (in lesser amounts than H1 histones) which bind to nucleosomes and modulate chromatin higher-order structure and functions [38][39][40]. Figure 6 presents immunostaining data for two HMG proteins (HMGN2 and HMGB2), illustrating the patterns in 0 mM and in 300 mM sucrose.…”
Section: Ki67 Segregates From Hyperosmotic Sucrose Congealed Mitotic mentioning
confidence: 99%
“…In the human protein microarray (protoarray) assay, [104] three topologically different model G4s were used. Top protein hits for all three or two of the three G4s included the following: ASXL1, a component of the polycomb complex PR-DUB (a histone deubiquitinase that mediates polycomb-target repression [105] ); the linker histone analogs HMGN1 and HMGN3, which modulate histone acetylation; [91,106,107] the linker histone analog HMGB2, which acts similarly to the above-mentioned HMGB1 but also participates in the demarcation of topologically associated chromatin domains by preventing aggregation of CCCTC-binding factor (CTCF); [108] the peptidylarginine deiminase 4 (PADi4), which mediates histone citrullination; [109] histone chaperones FACT (facilitates chromatin transcription) and BRD3 (bromodomain protein 3).…”
Section: G4s Might Directly Engage Architectural Chromatin Proteins mentioning
confidence: 99%
“…Recently, studies have demonstrated the contribution of the chromatin to nuclear rigidity and small deformations of the nucleus, whilst nuclear lamins and their connections with the nuclear envelope contribute mainly to larger deformations [11,12]. Likewise, it has been reported that the nucleosome disposition induced by histone tails and DNA linkers are crucial for nuclear rigidity [17,18]. In addition, others previously showed that chromatin condensation is associated with lower nuclear deformability in mesenchymal stem cells (MSCs), which reinforces the idea that chromatin controls a different biomechanical response than lamins [10,19].…”
Section: Chromatin Contribution To Nuclear Stiffnessmentioning
confidence: 99%